EFEKTIVITAS KOMUNIKASI AKUN INSTAGRAM @SEHATSURABAYAKU SEBAGAI MEDIA INFORMASI VAKSINASI COVID-19 MASYARAKAT KOTA SURABAYA - Yusni Nur Aini; Edy Sudaryanto (Sintesa, 2023)
The effectiveness of using Instagram as a medium of communication is an action to see the extentof effort in communicating through an Instagram in obtaining or producing an effect of achievinga predetermined goal. The study aims to determine how much the level of communicationeffectiveness of the Instagram account @sehatsurabayaku as an information medium for theCovid-19 vaccination of the people of the City of Surabaya by using the theory of CommunicationEffectiveness from Andre Hardjana which consists of 6 indicators, receiver or user, content,timing, media, format and source. Research sampling used the Random Sampling sampletechnique with a total of 100 respondents. The research data was obtained through thedissemination of questionnaires to Instagram followers @sehatsurabayaku. The data analysisused is descriptive quantitative using the SPSS Version 25 program. The results of the studyobtained a percentage result of 86.87%, which is included in the very effective category. So thatshows that the Instagram account @sehatsurabayaku become a very effective media as a mediumfor information on the Covid-19 vaccination of the people of the City of Surabaya.